Penerapan Model Pembelajaran Kooperatif Numbered Heads Together Kelas X SMK Negeri 1 Sibolga - Nurliani Siregar; Hisar Siregar; Sunggul Pasaribu; Imelda Butar-Butar; Ester Sitorus; Esti Sirait; Riana Lumbanraja; Sorta Nababan (Departement of Mathematics Education, 2023)
The NHT model is a type of cooperative learning method designed to influence student interaction patterns. NHT gives students more time to think answers and help each other. The research was conducted with a quantitative approach taking a Classroom Action Research (CAR) model. In its implementation, CAR is carried out in two cycles. Result of the NHT type of cooperative learning model to improve communication competence and teamwork for class X students at SMK Negeri 1 Sibolga, shows that student success has increased. At the end of cycle 1 the average score of the student group assignment was only 6.25. By the end of cycle II the average score of the assignments of the student group increased to 7.50. So that student learning achievement has exceeded the KKM score that has been set by the school, which is more than 7.00.